2015
DOI: 10.4238/2015.september.22.15
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and stability of genotypes of sweet sorghum by GGEBiplot and Toler methods

Abstract: ABSTRACT. Sweet sorghum has considerable potential for ethanol and energy production. The crop is adaptable and can be grown under a wide range of cultivation conditions in marginal areas; however, studies of phenotypic stability are lacking under tropical conditions. Various methods can be used to assess the stability of the crop. Some of these methods generate the same basic information, whereas others provide additional information on genotype x environment (G x E) interactions and/or a description of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…The lines BR501, CMSXS642, CMSXS643, and hybrid BSW80147 were highlighted for being late. This result is similar to that reported by de Figueiredo et al (2015). PH ranged from 1.36 to 3.49 m (Figure 1).…”
Section: Resultssupporting
confidence: 92%
“…The lines BR501, CMSXS642, CMSXS643, and hybrid BSW80147 were highlighted for being late. This result is similar to that reported by de Figueiredo et al (2015). PH ranged from 1.36 to 3.49 m (Figure 1).…”
Section: Resultssupporting
confidence: 92%
“…R² estimates above 75% were observed for the traits PH, PS PP and Brix (Table 1), which together to the quotient b allow inferring that these traits are subject to significant genetic gains into successive selection cycle. (Table 2), similar to the noticed by Sandeep et al (2011), Rani andUmakanth (2012) and Figueiredo et al (2015). The main cause of phenotypic correlation between two traits is the pleiotropism, property by which a gene affects more than one trait simultaneously; and linkage disequilibrium, nonrandom association between alleles from different loci (Mode & Robinson, 1959).…”
Section: Coefficient Of Experimental Variation (Cv E )supporting
confidence: 69%
“…Genotype × site interaction (P < 0.05) was also observed for most of the traits, except for juice extraction (EXT). Some studies on sweet sorghum have indicated the presence of the genotype × environment interaction for traits related to ethanol yield (ETH) (Umakanth et al 2012, Souza et al 2013, Elangovan et al 2014, Figueiredo et al 2015.…”
Section: Resultsmentioning
confidence: 99%